The rise of Skywalker - Carson, Rae (Star wars novel, 2020)
"The Resistance has been reborn. The spark of rebellion is rekindling across the galaxy. But although Rey and her fellow heroes are back in the fight, the war against the First Order, now led by Supreme Leader Kylo Ren, is far from over. Rey, Finn, Poe, and the Resistance must embark on the most perilous adventure they have ever faced. And this time, they're facing it together. With the help of old friends, new allies, and the mysterious guidance of the Force, the story that began in Star Wars: The Force Awakens and continued in Star Wars: The Last Jedi reaches an astounding conclusion."--Amazon